2018
DOI: 10.1371/journal.pntd.0006354
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication and predator presence overrule the effects of temperature on mosquito survival and development

Abstract: Adequate predictions of mosquito-borne disease risk require an understanding of the relevant drivers governing mosquito populations. Since previous studies have focused mainly on the role of temperature, here we assessed the effects of other important ecological variables (predation, nutrient availability, presence of conspecifics) in conjunction with the role of temperature on mosquito life history parameters. We carried out two mesocosm experiments with the common brown house mosquito, Culex pipiens, a confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…To determine effectiveness of the treatments, phosphate (PO 4 ) and nitrate (NO 3 ) concentrations were measured in the mesocosms (t = 12 days) using a similar procedure as described above. In mesocosms not receiving the eutrophication treatment, the so-called oligotrophic treatment, no food was added to mimic rainwater fed breeding containers with realistic nutrient availability [12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine effectiveness of the treatments, phosphate (PO 4 ) and nitrate (NO 3 ) concentrations were measured in the mesocosms (t = 12 days) using a similar procedure as described above. In mesocosms not receiving the eutrophication treatment, the so-called oligotrophic treatment, no food was added to mimic rainwater fed breeding containers with realistic nutrient availability [12].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that eutrophication and predation can present important bottom-up and top-down controls of local mosquito populations [8, 10, 12]. Eutrophication and the resulting increase in food availability for mosquito larvae increases their developmental rates, thus promoting higher numbers of adults emerging from temporary ponds [12, 13]. In contrast, the presence of predators can diminish population sizes of their prey [10, 12, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquitoes (order: Diptera, family: Culicidae) are known vectors for a wide variety of pathogens. The mosquito community composition is influenced by myriad of biotic and abiotic factors (e.g., resource availability, predation, temperature) that operate mostly at a local scale (Washburn, 1995;Reiter, 2001;Chase and Knight, 2003;Lafferty, 2009;Young et al, 2017;Schrama et al, 2018;Krol et al, 2019). A more comprehensive understanding of the drivers of mosquito community composition, may facilitate better management of mosquito communities (Beketov and Liess, 2007;Stresman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The two test sites were away from dense residential properties and artificial light sources due to abundances of mosquito activity. Many authors have found that temperature was the most relevant environmental parameter affecting the activity of adults of many mosquito species (Bidlingmayer , Rivas et al , Schrama et al ). Lighting has also been shown to have an effect on the landing periodicity of mosquitoes (Farnesi et al , Rivas et al ).…”
Section: Discussionmentioning
confidence: 99%